Female Genital Mutilation dan Pertanggungjawabannya Menurut Hak Asasi Manusia - Masuku, Akhmad Iqbal Jihad; Anwar, Arman; Tuhulele, Popi (Faculty of Law, Universitas Pattimura, 2024)
Introduction: This study examines the practice of Female Genital Mutilation (FGM), involving cutting, scraping, or piercing female genital organs with the aim of partial or total removal, often based on cultural reasons. It is estimated that over 200 million women worldwide have undergone FGM.Purposes of the Research: The research evaluates whether FGM can be considered a violation of international Human Rights (HR) and whether countries and perpetrators of FGM can be held accountable under international law.Methods of the Research: Using a normative legal research method, focusing on international HR instruments such as the Convention on the Elimination of all forms of Discrimination Against Women (CEDAW).Results of the Research: The study finds that FGM is inconsistent with international HR values and can be categorized as a violation of HR against women. The study emphasizes the state's responsibility to protect women from this harmful practice and suggests the imposition of sanctions on perpetrators. However, it also highlights the complexity of addressing FGM due to variations in types and practices across different countries. Therefore, criminalization is not always seen as an ideal solution, stressing the need for a holistic approach that integrates health, cultural, and legal aspects. Efforts to prevent FGM are expected to align with international HR values without discriminating against specific cultures while preserving existing community traditions